Land Productivity and Plot Size : Is Measurement Error Driving the Inverse Relationship? - Desiere, Sam (Elsevier, 2017)
This paper revisits the decades-old puzzle of the inverse plot-size productivity relationship (IR), which states that land productivity decreases as plot size increases. While existing studies define land productivity or yields as self-reported production divided by plot size, we consider an alternative approach to estimating yields based on crop cuts. The crop-cut method entails measuring and harvesting randomly selected subplots by trained technicians, and is recommended by the Food and Agricultural Organization for the accurate measurement of crop production. Using data of rural Ethiopia, our analysis indicates that the IR is strong when based on self-reported production, but disappears when based on crop-cut estimates. Our inference from these findings is that the IR is an artifact of systematic over-reporting of production by farmers on small plots, and under-reporting on larger plots. We also discuss how rejecting the inverse plot-size productivity relationship has significant implications for the inverse farm-size productivity relationship.